Dos dedahan radiasi dan penglihatan warna pekerja di Mint - Bashirah,; Sharanjeet Kaur,; A.E. Ariffin, (Department Of Community Health, Faculty of Medicine, Universiti Kebangsaan Malaysia, 2000)
According to the Atomic Energy Licensing Act 1984, the annual radiation exposure dose limit for the whole body of workers is 50 mSv. The annual dose measured from film badges worn by radiation workers at Malaysian Institute for Nuclear Technology (MINT) ranged from 0.2 mSv to 22.3 mSv (mean 1.35 + 2.77 mSv). For exposure of hands, the permissable dose limit is 500 mSv. For radiation workers at MINT, the hand exposure dose measured from a thermoluminent-dosemeter ring worn on the right and left finger ranged from 0 to 257.2 mSv (mean 5.78 + 28.60 mSv) and 0 to 155.5 mSv (mean 4.50 + 17.62 mSv) respectively. All measured values were found to be still below permissable levels. In spite of that, colour vision testing using Fansworth Munsell 100-Hue test (FM100-Hue) conducted on 187 workers at MINT (of which 105 were radiation workers and 82 were non-radiation workers)revealed a polar decrease of hue discrimination especially for the blue-yellow axis, when compared to 40 normal subjects in the control group. Mean of square root of total error scores (AITES) for radiation workers (7.08 + 2.42) and non-radiation workers (7.03 + 2.06) showed significant differences when compared to the control group (4.18 + 0.89) ) (ANOVA F(2, 224)=32.32, p<0.05) Analysis of results of FM100-Hue test using the Vingrys method revealed colour vision defects in 46.3% of radiation workers and 33.3% of non-radiation workers. A weak but significant correlation was found between the potential for colour vision defect and duration of work. It can be deduced from this study that workers at MINT are at a risk of acquiring colour vision defects as a result of cumulative effects from exposure to radiation (for the duration of their work at MINT).